Peran Penting Kualitas Pelayanan Bagi McDonald's Dalam Meningkatkan Kepuasan Pelanggan - Daniel Christover Silaban, Wiltasar; Hafiy Prayitno, Muhammad; Mizar Pratama, Husein (Shofanah Media Berkah, 2024)
This study aims to observe and determine the important role of service quality in increasing customer satisfaction. Basically, creating customer satisfaction is a business goal that can be done by retaining customers to gain profit. One of the restaurants that will be studied is McDonald's. McDonald's is one of the largest fast food franchises in the world, where fast and practical service makes McDonald's popular with the public.